Kilka uwag o mikrotoponimii dawnej ziemi chełmskiej - Koper, Mariusz (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
This paper presents selected issues related to the 18th century toponyms in the region of Chełm. Manuscript sources report microtoponymic formations that display inconsistency in the implementation of the then-contemporary standards of spelling and frequent alternations in the spelling of the particular names. The causes need to be sought in language interferences, limited language competence and the bilingualism of the authors. Searching for the appropriate classification of the analysed toponyms, the author created his own classification, which is mostly based on modifications of the existing proposals. This choice is dictated by the specificity and diversity of the microtoponymic system under analysis. It is also evoked by the lack of a universally accepted and uniform system of toponyms.